Writing Victimhood - Signe Uldbjerg (The Royal Danish Library, 2021)
Non-consensual sharing of intimate images, here called digital sexual assault (DSA), has been a heavily debated subject in Denmark over the past few years. In the polarized public and academic debate, DSA victims are often either subjected to victim blaming or portrayed as ‘broken’ victims with little agency and hope of redemption. This article presents a methodology for working with DSA victims to construct their own alternative and empowering stories of victimhood. Through an experimental methodology based on creative writing, I have included three young women in a process of collectively developing and exploring aspects of their experiences with DSA. With this methodology, I aim to combine activism and research in investigating DSA and actively supporting victims in constructing progressive stories of victimhood; stories that, as activism, work in opposition to oppressive discourses, and, as research, offer insights into complex experiences of victimhood. The article ends in a discussion of change as the prospect of activist research and experimental methodologies and concludes with a “manifesto for writing victimhood” stating activist aims that encourage and value social, personal and political change in and through research.